Measuring fish metabolism – science and practice of development in fish feeding: A review - Hancz, Csaba; Varga, Dániel (Acta Agraria Kaposváriensis, 2017)
Since costs related to feeding comprise determining part of production costs in aquaculture, as in any other branch of animal production, innumerable studies aimed to give information about the feed utilization were done also for fish. The great majority of literature discusses only the simplest indicators as feed conversion ratio (FCR), feed efficiency ratio (FER), protein efficiency ratio (PER) and productive protein value (PPV). One of the key research areas however that made possible the impressive growth of aquaculture in the last decades certainly was the extensive development of feeds based on sophisticated knowledge of nutrient requirements of more and more fish species. The main goal of this literature review was to focus on digestibility of nutrients, its measurement methods and to survey the main directions of contemporary research activity in this field.In conclusion, determination of apparent digestibility coefficients (ADC) became an everyday practice of experimental methodology in fish nutrition studies, although there are no standardized methods, neither in marker use nor in feces collection, just to mention two from the most crucial questions. Testing and evaluating new alternative protein and energy sources to minimalize the use of fishmeal (FM) and fish oil (FO) needed to develop the requirement at ration level (RRL) method to determine adequate daily ration and also the diet replacement method (DRM) and ingredient replacement method (IRM) for ingredient inclusion in studies on digestibility. Metabolomics and nutrigenomics offer new ways of approximation in areas of primary importance in the future development of aquaculture.
Keywords: fish; metabolism; digestibility; omics